Caracterização de colágenos tipos I e III no estroma do carcinoma de células escamosas cutâneo em cães - Bedoya, S. A.O.; Conceição, L. G.; Viloria, M. I.V.; Loures, F. H.; Valente, F. L.; Amorim, R. L. [UNESP]; Silva, F. F. (FapUNIFESP (SciELO), 2016)
Squamous cell carcinoma (SCC) is a malignant epithelial tumor that affects dogs and several other species, including humans. The SCC occurs in various anatomical sites and can develop metastasis. The aim of this study was to characterize types I and III collagen fibers in the stroma of cutaneous SCC in dogs. For this work 44 paraffin-embedded samples with previous diagnostic of SCC were used. Samples were processed and evaluated histologically with hematoxylin/eosin to confirm the diagnosis and classification of cell differentiation degree and with Picrosirius for observation of types I and III collagen. Type III collagen expression was higher in well-differentiated SCC. The role of type III collagen in cancer is not very clear and factors other than cell differentiation degree may be involved in its expression and determine its importance in tumor biology.
Characterization of types I and III collagen in the stroma of cutaneous squamous cell carcinoma in dogs
Keywords: Epithelial neoplasm; Hematoxylin/eosin; Picrosirius; Skin